2006
DOI: 10.1097/01.scs.0000246502.69688.60
|View full text |Cite
|
Sign up to set email alerts
|

Submandibular Ectopic Thyroid Gland

Abstract: Ectopic thyroid glands are generally a rare entity appearing mostly in the cervical midline (90% of the cases) and even more rarely in other anatomical sites (10%). We present the case of an ectopic submandibular thyroid gland. An 81-year-old woman was referred to our department with a history of right-sided submandibular swelling. Preoperative FNA revealed benign ectopic thyroid tissue. The patient was submitted to resection of the mass. Histological examination of the specimen confirmed the diagnosis. A subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…A lingual location is most common, accounting for 90% of the reported cases [1,3,5,6,[8][9][10]. Other sites rarely involved are the mediastinum, lungs, porta-hepatis system, duodenum, esophagus, heart, breasts, and intra-tracheal area [1][2][3][4][5][6][7][8]. Presence of ectopic thyroid tissue in the submandibular region is extremely rare [1,3,4,[7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A lingual location is most common, accounting for 90% of the reported cases [1,3,5,6,[8][9][10]. Other sites rarely involved are the mediastinum, lungs, porta-hepatis system, duodenum, esophagus, heart, breasts, and intra-tracheal area [1][2][3][4][5][6][7][8]. Presence of ectopic thyroid tissue in the submandibular region is extremely rare [1,3,4,[7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Other sites rarely involved are the mediastinum, lungs, porta-hepatis system, duodenum, esophagus, heart, breasts, and intra-tracheal area [1][2][3][4][5][6][7][8]. Presence of ectopic thyroid tissue in the submandibular region is extremely rare [1,3,4,[7][8][9][10]. According to a recent study [8], similar cases of ectopic thyroid tissue have been reported in submandibular space.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations